(untitled) (Circe de clásicos y modernos, 2022)
This paper examines the affective, emotional, and ideological questions raised by the practice of evidentiary torture (basanos) as necessity (anangkê). It proposes that competing ideas about its truth-value in Athenian forensic oratory reflect a degree of ambivalence sufficient to indicate that the Athenians (can) recognize the inherent unreliability of the slave’s tormented body and mind to reveal the truth. In Prometheus Bound, the torture of Prometheus is dramatized as brutal coercion by Zeus’ authoritarian state and set against the ‘coercion’ exercised by the bonds of kinship and emotional attachment. As such it engenders unbending anger on both sides and fails to coerce Prometheus to speak. The juxtaposition of the two genres establishes the unreliability of torture for extracting information along with a recognition that the criteria of exclusion for rendering bodies torturable are arbitrary, as are the rights they help maintain in the interest of Athenian exceptionalism. Fully embracing these recognitions would necessitate a new politics of care and fundamental reorganization of the civic community to expand ‘kinship’ and the bonds that compel mutual recognition and political inclusion. The paper closes by turning to the use of torture by the CIA in the context of the American war on terror to elucidate the persistence of discourses of necessity in contemporary politics of righteous anger and brings forth similar misrecognitions in the interest of American exceptionalism.